2016
DOI: 10.1093/mnras/stw1841
|View full text |Cite
|
Sign up to set email alerts
|

MOCCA-SURVEY database I. Accreting white dwarf binary systems in globular clusters – I. Cataclysmic variables – present-day population

Abstract: In this paper, which is the first in a series of papers associated with cataclysmic variables and related objects, we introduce the CATUABA code, a numerical machinery written for analysis of the MOCCA simulations, and show some first results by investigating the present-day population of cataclysmic variables in globular clusters. Emphasis was given on their properties and the observational selection effects when observing and detecting them. In this work we analysed in this work six models, including three w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(84 citation statements)
references
References 87 publications
(142 reference statements)
6
77
1
Order By: Relevance
“…In agreement with the results found by Belloni et al (2016a) for a population of binaries with the same Kroupa (1995Kroupa ( , 2013 initial conditions adopted here, we find that for all of the CVs dynamics plays a key role in their evolution towards becoming a CV (see Belloni et al 2016a for further discussion). We can, however, distinguish two groups in the CV population: one group consisting of CVs formed from primordial binaries which during the cluster evolution had their orbital parameters affected by encounters with other binaries and single stars, but their components at 12 Gyr are still the initial ones (hereafter we refer to this group as the P(rimordial) group), and another group consisting of CVs formed instead from primordial binaries which suffered at least one exchange encounter during which one of the initial components was replaced by either the interacting single star or one of the components of the interacting binary (we refer to this group as the E(xchange) group).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with the results found by Belloni et al (2016a) for a population of binaries with the same Kroupa (1995Kroupa ( , 2013 initial conditions adopted here, we find that for all of the CVs dynamics plays a key role in their evolution towards becoming a CV (see Belloni et al 2016a for further discussion). We can, however, distinguish two groups in the CV population: one group consisting of CVs formed from primordial binaries which during the cluster evolution had their orbital parameters affected by encounters with other binaries and single stars, but their components at 12 Gyr are still the initial ones (hereafter we refer to this group as the P(rimordial) group), and another group consisting of CVs formed instead from primordial binaries which suffered at least one exchange encounter during which one of the initial components was replaced by either the interacting single star or one of the components of the interacting binary (we refer to this group as the E(xchange) group).…”
Section: Resultssupporting
confidence: 91%
“…We finally point out that the presence of a tail of more massive CVs in the E group is consistent with the results of Shara & Hurley (2006) and Belloni et al (2016a) who also found that the population of CVs affected by exchange encounters included a population of more massive CVs. CVs with main sequence donor larger than 0.1 M⊙ belong mainly to the E group and have, in general, younger ages than those with a donor less massive than 0.1 M⊙.…”
Section: Resultssupporting
confidence: 90%
“…textsccocoa can also be significantly important for observers that would like to make use of interesting theoretical results and check whether observations can verify those results. For instance, a number of numerical simulations predict expected number of various exotic objects like cataclysmic variables (Belloni et al 2016), blue stragglers ) and other interesting objects. With cocoa, it is possible to check whether such predicted numbers of exotic objects and their spatial distribution can be observationally recovered.…”
Section: Discussionmentioning
confidence: 99%
“…Binary parameters for S models had 'standard' distributions (uniform mass ratio (q) distribution, thermal eccentricity distribution and log-normal or uniform in log semi-major axis distribution). Table 3 summarizes the initial and 12 Gyr properties of these cluster models that have have also been described in Belloni et al (2016). Figure 7 shows the simulated I band image for the moderately dense K2 cluster projected at a distance of 5 kpc and Figure 8 shows CMDs for this model.…”
Section: Multiband Photometry With Cocoa and Initial Binary Parameter (mentioning
confidence: 99%
“…Theoretically, there are many products that can be dynamically formed through the encounters of hard binaries in GCs, which include intermediatemass black holes (IMBH; Miller & Hamilton 2002;Portegies Zwart & McMillan 2002;Portegies Zwart et al 2004;Gürkan et al 2004;Giersz et al 2015;Fragione et al 2018), binary compact objects that can contribute to gravitational wave sources (Portegies Zwart & McMillan 2000;Downing et al 2010;Samsing et al 2014;Rodriguez et al 2015Rodriguez et al , 2016Askar et al 2017;Hong et al 2018;Ye et al 2020), low-mass X-ray binaries (LMXBs; Rasio et al 2000;Ivanova et al 2010;Giesler et al 2018;Kremer et al 2018a), millisecond pulsars (MSPs; Ivanova et al 2008;Ye et al 2019b), cataclysmic variables (CVs; Ivanova et al 2006;Shara, & Hurley 2006;Belloni et al 2016;Hong et al 2017;Belloni et al 2017Belloni et al , 2019, coronally active binaries (ABs) and blue straggler stars (BSS; Fregeau et al 2004;Chatterjee et al 2013). As GCs aged, it is natural to infer that more and more binary burning products be generated in the core of GCs.…”
Section: Introductionmentioning
confidence: 99%